KAJIAN MORALITAS DALAM NOVEL TUHAN IJINKAN AKU MENJADI PELACUR KARYA MUHIDIN M DAHLAN - Nilatul Izzah; Sunu Catur Budiyono (Universitas PGRI Adi Buana Surabaya, 2018)
The research has target for describing moral value that is first figure and communitymoral there are from novel Tuhan Ijinkan Aku Menjadi Pelacur. Morality is quality ofhuman behavior that shows one's behavior is right or wrong, good or bad. In order to makethis research being analyzed, so the researcher use the theory of Thomas Lickona,whichemphasize in three things, those are to know the value of moral, moral feeling, and moralbehavior. Method for this research is hermenutik method (interpreting text). Data and dataresource are the moral value of God bless Me be Prostitute novel by Muhidin M. Dahlan.Data collection technique is using repeat reading, make notes and data classification. Dataanalysis technique is using interpretation, explanation, description, and make conclusion.Data is divided by subs chapter based on the problem and research purpose. Data thatalready been interpreted then it described in an essay as the result. The conclusion by thisresearch is 1) moral knowledge there is moral awareness, knowing moral value, takeperpective, logical of moral and self knowledge from novel “Tuhan Ijinkan Aku MenjadiPelacur” 2) the attitude of moral is moral feeling, conscience, self regard, empathy, good love, self control, and humble. 3) the action of moral is interest, desire, andfigure habits and community. All of the conclusion has been found in the first figure andcommunity from novel “Tuhan Ijinkan Aku Menjadi Pelacur” novel by Muhidin MDahlan.